2009
DOI: 10.1038/jhg.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic bases for non-syndromic hearing loss among Chinese

Abstract: Deafness is an etiologically heterogeneous trait with many known genetic, environmental causes or a combination thereof. The identification of more than 120 independent genes for deafness has provided profound new insights into the pathophysiology of hearing. However, recent findings indicate that a large proportion of both syndromic and non-syndromic forms of deafness in the Chinese population are caused by defects in a small number of genes. Studies of the genetic epidemiology and molecular genetic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 141 publications
1
49
1
Order By: Relevance
“…9 Recently, the genetic causes of NSHL in Jews, Japanese and Chinese populations have been described. [10][11][12] In this survey, we emphasized the importance of identifying the genetic bases of NSHL and summarized the published data on the frequency of gene mutations in various loci studied in Iran; we provided counseling criteria for the patients. The distribution of the gene mutations was also shown.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, the genetic causes of NSHL in Jews, Japanese and Chinese populations have been described. [10][11][12] In this survey, we emphasized the importance of identifying the genetic bases of NSHL and summarized the published data on the frequency of gene mutations in various loci studied in Iran; we provided counseling criteria for the patients. The distribution of the gene mutations was also shown.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the A1555G mutation varies in nonsyndromic hearing-impaired populations by ethnicity: 2.9%-5.3% in Asian patients; 0.6%-2.5% in Caucasian deaf populations (Ouyang et al, 2009). In our study, the 1555A > G mutation was found in 0.9% (2/217) patients as a homoplasmic mutation, and at least one patient had a significant history of ototoxic medication exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial tRNA Ser (UCN) (MTTS1) gene appears to be a significant mitochondrial DNA (mtDNA) mutation locus associated with nonsyndromic sensorineural hearing loss (NSHL). Four deafness-associated mutations, A7445G, 7472insC, T7510C, and T7511C, have been identified in this gene (Ouyang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations